Implementation AHP Method in Selection of Outstanding Students at MI Sirojul Athfal 1 Bogor - Sulaeman Hadi Sukmana; Syifa Fauziah; Sucitra Sahara; Erma Delima Sikumbang; Rizqi Agung Permana (Universitas Medan Area, 2022)
At the beginning of 2020, precisely in March 2020, the government announced that Indonesia was affected by the Covid-19 outbreak. Since then, Indonesia has also been faced with a pandemic period, where all sectors of life have been affected, including the education sector. The primary school of MI Sirojul Athfal 1 Bogor conducts learning from home, this causes a lack of effective learning between teachers and students, and teachers find it difficult to determine student achievement. The Decision Support System (DSS) is one system that is able to assist researchers in making decisions accurately and in accordance with the objectives in determining outstanding students at the school. The Analytical Hierarchy Process (AHP) is capable of solving complex multi-criteria problems. From the results of this study and calculations carried out using the Expert Choice tool, it was concluded that the highest priority score was obtained by Muamar students with a value of 0.447. From this study, the results of the CR hypothesis for all criteria value are less than 0.1 or less than 10%, therefore the overall hierarchy produces consistent values.